Facebook i społeczne konstrukcje narcyzmu (o tożsamości zamkniętej w celi wizerunku) - Melosik, Zbyszko (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This text looks at the role of Facebook in (re)constructing identities in the contemporary society. The author focuses on Facebook-promoted image-based strategies of autopresentations in the context of the phenomenon of narcissism. He analyses the role of Facebook against the increasing tendency to move friendship from within the human being to the surface. This text is situated within the framework of critical pedagogy and the theory of social constructivism.
Keywords: autoprezentacja; Facebook; narcyzm; tożsamość; wirtualność